Focos de treinamento gerencial formal: percepção de gerentes de restaurantes da cidade de João Pessoa - Egito, Lilian Dias Nicacio Cruz do (2011)
The constant changes in the economic and social updates and require flexibility in the workplace, both in industry and services sector. In the latter, it is essential to good professional preparation, because of its good performance and good service, the results of customer satisfaction and loyalty. Given this, it becomes clear that the positioning takes formal training as a contributor to professional development and thus for organizational development. Given this, the present study aimed to demonstrate the main focuses of the need for formal training in accordance with the perception of managers of restaurants in the city of Joao Pessoa, based on the context of rationalization of work processes (production management) and development people. To pay attention to the objectives of the study the type of inquiry was used survey, when a basic / descriptive approach is adopted, by means of application of semistructured questionnaires, near 154 managers of restaurants of the border of the above-mentioned city. The instrument used was a structured questionnaire that investigated the activities of the managers in the workplace, the level of difficulty in performing them and the need for involvement or participation in formal training, for better performance of those activities. The method of data treatment applied was anchored on the use of SPSS software, through which he obtained, in addition to the frequencies and percentages, t-tests and Pearson correlation tests. The results show that in their daily lives, respondents develop a range of management activities distributed among the centers of production management and people development, and more activities are contained in this second focus, and that it has a more prominent when pointed out the activities that result in greater difficulty in achieving it. Still obtained as a result of the fact that the majority of respondents participated in formal training financed by the companies they work for and that, perhaps due to this participation, there is little interest in participating in further training. However, in response to the overall objective of this study revealed that, when they point to the need for formal training, managers also perceive as necessary to carry out training activities contained in both the focus of management in production and development of people. Finally, we present some suggestions and recommendations, aiming to contribute a better planning of formal management training, through the perspective of the managers themselves.